Ratcheting Strain Accumulation Due to Asymmetric Cyclic Loading of Zircaloy-2 at Room Temperature - R.S., Rajpurohit; Srinivas, N.C. Santhi; Singh, Vakil (Elsevier B.V., 2016)
Asymmetric stress cycling leads to accumulation of plastic strain which is called as ratcheting strain. The problem is generally associated with nuclear fuel cladding materials used in nuclear power plants and in pressurized pipe lines. In the present investigation asymmetric stress controlled fatigue tests were conducted with three different parameters namely, mean stress, stress amplitude and stress rate (keeping two parameter constant and varying third parameter) to see the plastic strain accumulation and its effect on fatigue life of Zircaloy-2 at room temperature. The tests were conducted with mean stress varying from 80 to 150 MPa, stress amplitude varying from 270 to 340 MPa and stress rate varying from 30 to 750 MPa/s respectively. The experimental outcomes show that with increase in mean stress and stress amplitude, the ratcheting strain accumulation increases with reduction in fatigue life. However, increase in stress rate leads to improvement in fatigue life of the material due to small ratcheting strain accumulation. Cyclic softening is observed during initial cycles for lower values of mean stress and stress amplitude and cyclic hardening is predominant for higher values of mean stress and stress amplitude. However, cyclic hardening is observed with increase in stress rate.
Keywords: asymmetric stress cyclic loading; Mean stress; plastic strain; ratcheting strain; stress amplitude; stress rate; Zircaloy-2